Analysis Of The Influence Of Communication Ethics In Business Competition In The Gen-Z - M. Ridho Al Aziz; Muhammad Rafli Hudhawi Nasution; Aditya Rahman Ginting; Panca Syahputra; Muhammad Yuda Hendrawan (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
know How influence Analysis The Effect of Communication Ethics In Competition Business in the Gen-Z Era . Method research Dr study This use method study study qualitative. Results show that ethics communication play role crucial in create mark period long for company in the middle market dynamics and the environment continuing business growing. Generation Z, which is consumer active and potential employees in this era, have high expectations to communicating company with honest, transparent, and respectful values ethics. In competition growing business strict, company must understand that ethics communication is more from simply approach strategic, however reflect identity and character company in a manner whole. Good communication ethicswill build trust customer, strengthen reputation company, and improve loyalty consumer. Besides that's ethics positive communication as well factor towing for candidate Gen-Z employees who are looking environment quality and practical work values ethics. An understanding company mark important ethics communication in build culture inclusive and respectful company diversity will interesting talents best in competition get power quality work. In the digital age, messages and information can spread with fast through social media and other online platforms. because tha , business must very be careful with ethics communication them, avoid practices that don't ethical, and caring reputation them to stay positive .